Two New Species of Cyphocaris (Amphipoda, Amphilochidea, Cyphocarididae) From Water Columns Above a Methane Seep in the South China Sea - Wang, Yanrong; Sha, Zhongli; Ren, Xianqiu (Frontiers in Marine Science, 2022)
The Formosa Ridge methane seep is one of three known active methane seepage areas discovered on the northern slope of the South China Sea. Cyphocaris Boeck, 1871 is a genus of pelagic amphipods. Two new species of Cyphocaris collected from water columns above the Formosa Ridge methane seep are reported in present study. Cyphocaris lubrica sp. nov. collected at a depth of 1118 m is characterized by pereonite 1 dorsal projection not extending beyond head, and the pereopod 5 having a spur beyond pereonite 7. Cyphocaris formosa sp. nov. collected at a depth of 500–800 m is characterized by well-developed pereonite 1 dorsal projection extending beyond head and pereopod 5 without spur. The present work describes these two new species and compares them with closely related species, and provides a modified key of world Cyphocarididae species.